Accessibility of E-government Services for Persons with Disabilities in Developing Countries- The Case of Ghana - Agangiba, Millicent Akotam (Department of Information Systems, 2020)
Several benefits have been attributed to E-government, including the potential to promote independence and belongingness for persons with disabilities (PWD) by enhancing participatory and inclusive governance. Hitherto, government services that required several and long journeys followed by long queues waiting for service at government offices can now be accessed online irrespective of the geographical location via E-government services. As a result, developing countries like Ghana continue to commit resources to the implementation of E-government to harness the associated benefits. Accessibility has been acknowledged, by both practitioners and those in academia, as a key consideration to prevent disparities among citizens which may put PWD at risk of exclusion. However, providing solutions to accessibility challenges for PWD has consistently proven difficult in most E-government implementation projects in developing countries. Therefore, this study investigates the accessibility of Egovernment services for PWD in Ghana with the aim of identifying how key E-government stakeholders perceive accessibility and the contextual drivers that lead to the exclusion of PWD in the development of E-government services. Also, this study seeks to understand if and how these stakeholders and contextual drivers reinforce the exclusionary process. The study employed an interpretive, inductive approach, with sensitising concepts from Egovernment accessibility literature, and the social exclusion framework. Multiple data collection methods were used, namely; observations as a preliminary step to obtaining a better understanding of how the visually impaired use ICTs; interviews as the primary data collection technique from 37 participants; and document analysis. The study involved 3 groups of participants: the visually impaired, E-government web developers and government officers. Data analysis was carried out in two phases- firstly thematic analysis was used to report on perceptions of government officers and developers on accessibility and the experiences of PWD. Contextual drivers impeding accessibility and affecting accessibility experience of PWD were also derived from the thematic analysis. Secondly, E-government and disability policy documents mentioned in interview discussions were analysed using content analysis. The findings of the content analysis were used to validate, clarify and to conduct post-interview checking. The findings show that government officers and developers play a key role in the development of E-government services. Whilst Government officers and developers were identified as powerful agents whose practices determined the accessibility of services that were developed; PWD were side-lined and not involved in the E-government development project. Also, perceptions of government officers and developers on accessibility vary from those of PWD. While government officers and developers believe that with little assistance from third parties PWD can access E-government services, PWD perceive accessibility should offer them the independence to retrieve government information and engage in electronic transactions of their choice. Evidently, accessibility perceptions of E-government implementers differ from that of PWD. Further, the findings show that exclusion of PWD from E-government services is as a result of the intertwining of several contextual drivers, including political, socio-cultural, technological and personal. Political, socio-cultural and technological drivers influence the perceptions and practices of government officers and developers and determine their responses to the accessibility needs of PWD. Personal drivers limit the capabilities of PWD to access Egovernment services and impact on their accessibility experiences. Contextual drivers independently facilitate the exclusion of PWD; however, their interactions with government officers and developers shape their perceptions and constitute crucial exclusionary forces. These exclusionary forces when fed into the development of E-government services reinforce the exclusion of PWD. Given that personal drivers limit the capabilities of PWD, their inabilities to act as change agents reinforce their exclusion. Moreover, power differentials among stakeholders play a vital role in the exclusionary process. The study contributes to better understanding of influences on the E-government development process, how services become inaccessible and the accessibility challenges PWD face. Practically, the study has several implications on the development and implementation of E-government services in developing countries like Ghana. For example, the findings are useful to inform the political leadership on policies and structures to put in place to enhance the accessibility of Egovernment services for PWD.